The Phoebe A. Hearst Expedition to Naga ed-Deir, Cemeteries N 2000 and N 2500 - Davies, Vanessa, (Harvard Egyptological Studies ;, 2021)
The Phoebe A. Hearst Expedition to Naga ed-Deir, Cemeteries N 2000 and N 2500 presents the results of excavations directed by George A. Reisner and led by Arthur C. Mace. The site of Naga ed-Deir, Egypt, is unusual for its continued use over a long period of time (c. 3500 BCE-650 CE). Burials in N 2000 and N 2500 date to the First Intermediate Period/Middle Kingdom and the Coptic era. In keeping with Reisner's earlier publications of Naga ed-Deir, this volume presents artifacts in chapter-length studies devoted to a particular object type and includes a burial-by-burial description. The excavators' original drawings, notes, and photographs are complemented by a contemporary analysis of the objects by experts in their subfields.